2017
DOI: 10.1021/acs.jnatprod.7b00457
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Asarone-Derived Phenylpropanoids from the Rhizome of Acorus tatarinowii Schott

Abstract: Eight new (1a/1b, 2a, 3a, 4a/4b, and 5a/5b) and seven known (2b, 3b, and 6-10) asarone-derived phenylpropanoids, a known asarone-derived lignan (12), and four known lignan analogues (11 and 13-15) were isolated from the rhizome of Acorus tatarinowii Schott. The structures were elucidated via comprehensive spectroscopic analyses, modified Mosher's method, and quantum chemical calculations. Compounds 1-8 were present as enantiomers, and 1-5 were successfully resolved via chiral-phase HPLC. Compounds 1a/1b were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…It has been reported that the rhizome extract of Acorus tatarinowii Schott possesses various biological activities including hypoglycemic, antioxidant, anticonvulsive, antimicrobial, and anti‐epileptic properties, and activity against Alzheimer's disease (Gao et al, ). In previous studies, we found that the α‐asarone‐derived lignins extracted from Acorus tatarinowii Schott rhizome, TO and TN, can effectively inhibit RANKL‐induced osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the rhizome extract of Acorus tatarinowii Schott possesses various biological activities including hypoglycemic, antioxidant, anticonvulsive, antimicrobial, and anti‐epileptic properties, and activity against Alzheimer's disease (Gao et al, ). In previous studies, we found that the α‐asarone‐derived lignins extracted from Acorus tatarinowii Schott rhizome, TO and TN, can effectively inhibit RANKL‐induced osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Employed as a traditional Chinese medicine, the rhizome of Acorus tatarinowii Schott has low toxicity and is used to treat dementia, central nervous system‐associated disorders, rheumatosis, and other inflammatory diseases (Xu et al, ; Gao et al, ; Tian et al, ). Previous studies have investigated several extracts from Acorus tatarinowii Schott and found that the lignin‐like components, TO (Xu et al, ) and TN (Zhang et al, ), can both inhibit osteoclastogenesis; however, Tatarinan U (TU) and Tatarinan V (TV) lack this suppressive activity.…”
Section: Introductionmentioning
confidence: 99%
“…The α -glucosidase inhibitory assay was conducted as per a previous report [ 34 ]. Acarbose was used as the positive control.…”
Section: Methodsmentioning
confidence: 99%
“…[ 28 ] Modern pharmacologic studies have shown that extract of A tatarinowii Schott has a variety of biologic activities, such as antioxidant, anti-Alzheimer disease, antimicrobial, anticonvulsive, and antiepileptic effects. [ 29 ] Nevertheless, there is little evidence about of the potential mechanism of Chinese herbs for CSDH. The high proportions of L heterophyllus Sweet, S persicae , and A tatarinowii Schott which included in a single prescription suggested that they may play a crucial role in promoting CSDH absorption.…”
Section: Discussionmentioning
confidence: 99%